Economic integration and the structure of national institutions - Phedon Nicolaides (Intereconomics, 2012)
This study analyses institutional features national authorities should have in order to apply common policies effectively. It shows that the effective implementation of EU law and policy can be achieved without increased control. The article suggests that benchmarking of the results of the application of common rules by the national authorities and comparative assessment of their performance is more efficient.
Keywords: 330; EU-Recht; EU-Politik; Rechtsdurchsetzung; Institutionelle Infrastruktur; EU-Staaten